Mental Skills and their Relationship to Some Basic Skills of Sword Fencing Players for the Middle Euphrates Clubs in Iraq - Bushra Hussain Alwan; Jabbar Hzoar Mohammed; Qahtan Khudhair Abbas (Institute of Medico-legal Publications Pvt Ltd, 2021)
The importance of the research lies in identifying the level of mental skills of dueling sword weapon players,due to their close association with the ability to adapt to the different situations required by the strugglesand helps us determine the level of basic skills. Of the sword weapon players, the sword weapon, and theextent of the relationship between them and mental abilities for the purpose of modifying weaknesses anddeveloping strengths, which helps us to stand on an important aspect of the psychological aspects thatsupport the efforts of the trainers and those responsible for the training process in raising the sword weaponplayers to higher levels, and the most important results were not Statistically significant differences appearbetween the players of the research sample teams in all mental skills. The most important recommendation isthe need to work on developing the basic skills of Sword Duel players in a way that ensures advanced levels.